Autoria e plágio em trabalhos acadêmicos: políticas e ações de combate a contrafação no contexto universitário - Oliveira, José Gláucio Brito Tavares de (2016)
The academic production is a main activities of the superior education, because promotes the knowledge through scientific researches and enable the development of a society. However, the academic works elaboration sometimes is stained by the plagiarism practice. The academic counterfeit occurs when the author uses intellectual contents, in whole or in part, of the others authors and don‟t cite them, failing to provide the credits the work searched, injuring the ethics principles and the legal proportions that organize the law of copyright. From this principle that we don‟t need of the database collected in field research to verify existence of the plagiarism in the university environment, this dissertation is characterized as a bibliography research. The study indicated the causes that lead the students to plagiarism. The following are cited as causes: easy access the information provided by the technology; lack of the planning time dedicated to studies; inability of the textual production practice; failure of the individual conduct moral and the technic unfamiliarity of the concepts related to plagiarism as well as concession rules of the credits to authors researched. After analysis institutional policies at UFRN, that ensure the copyright protection and combating plagiarism, was possible to see that, despite the recommendation for the creation instruments of orientation and awareness of an ethical behavior and the honesty in the academic conduct, there are still few the products and services combating to plagiarism in the university context. To resolution of the educational gap, according to institutional politics, this work we intend to contribute to the creation of the instruments to help the academic community, in classroom, in class related the Methodology of the Scientific Work, as well as training courses, reducing plagiarism cases in academic work at UFRN.